Epigenetic silencing of tumor suppressor Par-4 promotes chemoresistance in recurrent breast cancer - Mabe, Nathaniel W. (J Clin Invest, 2018)
Tumor relapse is the leading cause of death in breast cancer, largely due to the fact that recurrent tumors are frequently resistant to chemotherapy. We previously reported that downregulation of the proapoptotic protein Par-4 promotes tumor recurrence in genetically engineered mouse models of breast cancer recurrence. In the present study, we examined the mechanism and functional significance of Par-4 downregulation in recurrent tumors. We found that epithelial-to-mesenchymal transition (EMT) promotes epigenetic silencing of Par-4 in recurrent tumors. Par-4 silencing proceeded through binding of the EMT transcription factor Twist to the Par-4 promoter, where Twist induced a unique bivalent chromatin domain. This bivalent configuration conferred plasticity at the Par-4 promoter, and Par-4 silencing could be reversed with pharmacologic inhibitors of Ezh2 and HDAC1/2. Using an epigenome editing approach to reexpress Par-4 by specifically reversing the histone modifications found in recurrent tumors, we found that Par-4 reexpression sensitized recurrent tumors to chemotherapy in vitro and in vivo. Upon reexpression, Par-4 bound to the protein phosphatase PP1, caused widespread changes in phosphorylation of cytoskeletal proteins, and cooperated with microtubule-targeting drugs to induce mitotic defects. These results identify Twist-induced epigenetic silencing of Par-4 as a targetable axis that promotes chemoresistance in recurrent breast cancer.